Perceptions of self-medication of the population, during the covid-19 pandemic in Peru - Inostroza-Ruiz, Lusi Alberto (2021)
Background: Describe characteristics of self-medication of the population, in the context of the COVID 19 pandemic. Material and Methods: We carried out a cross-sectional survey with students in a major public Peruvian university. We measured perception of self-medication of the population, as well as characteristics, consequences, and associated factors. Results: A total of 274 students of Pharmacy and biochemistry filled in the questionnaire, 80.3% of which reported to know someone that self-medicated during the COVID-19 pandemic. 98.9 % of surveyed participants considered that the current pandemic increased self-medication practices in the population and that it occurred more frequently when people have symptoms associated with COVID-19 (65.4%). The medicines most frequently used were ivermectin (79.2%), azithromycin (71.2%) and hydroxychloroquine (38.7%). Conclusion: According to the surveyed participants, self-medication has increased in the general population during the COVID-19 pandemic. Strategies to prevent these practices are needed, as they could delay adequate medical care.